2011
DOI: 10.2298/hemind101122005j
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrochemical methods for the investigation of intergranular corrosion welded joint austenitic stainless steel 19Cr-9Ni

Abstract: Sensitization degree of the austenitic stainless steel welded joints was investigated by electrochemical methods of the double loop electrochemical potentiokinetic reactivation (DL EPR) in H2SO4 + KSCN solution, and by the measurement of corrosion potential of the steel in the drop of the solution of HNO3 + FeCl3 + HCl. The welded joints were tested by X-ray radiographic method in order to check the presence of the weld defects. Grain size of the base metal and the welded joints were determined by optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Based on the results shown in Figures and and in Table , it can be concluded that the base metal is resistant to intergranular corrosion, while the HAZ is slightly susceptible. In general, a stainless steel that is susceptible to intergranular corrosion is also susceptible to stress corrosion cracking; therefore, the DL‐EPR method can be used to estimate the susceptibility of a stainless steel to stress corrosion cracking …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results shown in Figures and and in Table , it can be concluded that the base metal is resistant to intergranular corrosion, while the HAZ is slightly susceptible. In general, a stainless steel that is susceptible to intergranular corrosion is also susceptible to stress corrosion cracking; therefore, the DL‐EPR method can be used to estimate the susceptibility of a stainless steel to stress corrosion cracking …”
Section: Resultsmentioning
confidence: 99%
“…In general, a stainless steel that is susceptible to intergranular corrosion is also susceptible to stress corrosion cracking; therefore, the DL-EPR method can be used to estimate the susceptibility of a stainless steel to stress corrosion cracking. [41,49] The SEM micrographs of the stainless steel surface after the intergranular corrosion testing are shown in Figure 3. A slight dissolution of the grain boundary areas in the HAZ occurred in the regions depleted in chromium, as it can be seen in Figure 3b.…”
Section: Results Of the Intergranular Corrosion Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…DL EPR metodu je razradio V. Čihal [6,12] i našla je primenu za ispitivanje sklonosti prema interkristalnoj koroziji ne samo austenitnih čelika [13], već i feritnih [7], duplex nerđajućih čelika [14], itd. DL EPR metoda se primenjuje za ispitivanje sklonosti zavarenih spojeva nerđajućih čelika prema interkristalnoj koroziji, kao i za ispitivanje sklonosti prema naponskoj koroziji [11].…”
Section: Slika 1 Primer Ispitivanja Sklonosti Prema Interkristalnoj unclassified
“…Also, the ratio of the current peak value in the reverse part of the loop (reactivation) and the passivation current peak value in the activation part of the loop can represent a measure of the susceptibility to intergranular corrosion. DL EPR method can be applied with certain modifications to test susceptibility to intergranular corrosion of other types of stainless steels [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%